2003
DOI: 10.1046/j.0031-0239.2003.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

The A‐mode sutural ontogeny in prolecanitid ammonoids

Abstract: ABSTRACT. The generally accepted theory of a U-mode sutural ontogeny of prolecanitid ammonoids and their descendants is refuted. The basic suture formula of the order Prolecanitida is E A L U I (not E L U 2 U 1 I), resembling that of derived members of the suborder Tornoceratina (their phylogenetic ancestors), and of the suborder Goniatitina. During phylogeny of the prolecanitids, secondary umbilical lobes are introduced and lead to multilobate forms. In early ceratites, the original L lobe disappeared, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 0 publications
0
67
0
Order By: Relevance
“…Figures in brackets are dimensions as a percentage of the diameter. The suture terminology is that of Korn et al (2003): E = external lobe; A = adventive lobe (= lateral lobe, L, of Kullmann & Wiedmann, 1970); U = umbilical lobe; I = internal lobe.BMNH: The Natural History Museum, London. SAM: The South African Museum, Cape Town.…”
mentioning
confidence: 99%
“…Figures in brackets are dimensions as a percentage of the diameter. The suture terminology is that of Korn et al (2003): E = external lobe; A = adventive lobe (= lateral lobe, L, of Kullmann & Wiedmann, 1970); U = umbilical lobe; I = internal lobe.BMNH: The Natural History Museum, London. SAM: The South African Museum, Cape Town.…”
mentioning
confidence: 99%
“…However, the ontogeny of the suture line displays significant differences between Acrocanites and the prolecanitids, particularly in the timing of the introduction of new lobes and their shapes. Prolecanitid ammonoids show a rapid ontogenetic unfolding of suture characters, and the full number of lobes is reached in a rather early growth stage, as Korn et al (2003b) showed for Becanites africanus. In contrast, Acrocanites has a very slow ontogeny of sutural elements, with the full lobe number reached only in the sixth or seventh whorl.…”
Section: Figures 9 10mentioning
confidence: 99%
“…Korn (2010) published the key for the description of the species, including explanation of methods. Sutural terminology follows Korn et al (2003b Genus definition. Imitoceratinae with large discoidal conch, reaching a conch diameter of 150 mm.…”
Section: Systematic Palaeontologymentioning
confidence: 99%
“…The key for the description of the species, including explanation of methods, is published in this volume by Korn (2010). Sutural terminology follows Korn et al (2003).…”
Section: Systematic Palaeontologymentioning
confidence: 99%